Biomineralization: Encapsulation of Plant Viral Particles in Calcite Crystals (Adv. Biosys. 5/2018). Issue 5 (14th May 2018) - Al‐Handawi, Marieh B.; Commins, Patrick; Shukla, Sourabh; Didier, Pascal; Tanaka, Masahiko; Raj, Gijo; Veliz, Frank A.; Pasricha, Renu; Steinmetz, Nicole F.; Naumov, Panče
Abstract : Ionic inorganic matrices such as calcite are known to occlude ions, organic molecules and proteins, and this process is at the core of biomineralization. In article number 1700176, by using labeled cowpea mosaic virus, Panče Naumov and co‐workers demonstrate that calcite can occlude biomolecules as large as viruses up to several percent by mass. The results can be applied to thermal stabilization of vaccines towards elimination of the "cold chain".